2018
DOI: 10.1167/iovs.18-24562
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1 Inhibits Corneal Allograft Rejection in High-Risk Corneal Transplantation

Abstract: RvE1 treatment improves allogeneic corneal graft survival in a high-risk corneal transplantation model via inhibiting the Th1/Th17-related inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…RvE1 exerts bioactivities of antiinflammation, pro-resolving, and tissue protection by binding to its protein-coupled receptor, ChemR23, on various cells, including monocytes, macrophages, dendritic cells, NK cells and endothelial cells (19). Specifically, RvE1 induces an antiinflammatory effect, both acutely and chronically, by blocking the production of proinflammatory cytokines (20), inhibiting neutrophil transendothelial migration (17) and enhancing phagocytosis of microbial particles and apoptotic neutrophils (21). Apart from inflammation mediation, RvE1 also functions protectively by accelerating the restoration of endothelium function (22), alleviating tissue damage (23) and promoting bone preservation (24).…”
Section: Introductionmentioning
confidence: 99%
“…RvE1 exerts bioactivities of antiinflammation, pro-resolving, and tissue protection by binding to its protein-coupled receptor, ChemR23, on various cells, including monocytes, macrophages, dendritic cells, NK cells and endothelial cells (19). Specifically, RvE1 induces an antiinflammatory effect, both acutely and chronically, by blocking the production of proinflammatory cytokines (20), inhibiting neutrophil transendothelial migration (17) and enhancing phagocytosis of microbial particles and apoptotic neutrophils (21). Apart from inflammation mediation, RvE1 also functions protectively by accelerating the restoration of endothelium function (22), alleviating tissue damage (23) and promoting bone preservation (24).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the first to compare multiple aspects of corneal rejection between M1- and M2-dominated immune response models, namely C57BL/6J and BALB/c mice. These mouse strains are two of the most widely used models for rejection studies [7-9, 12, 24, 25, 27, 44, 45]. The results of our study indicate that these studies deserve cautious interpretation.…”
Section: Discussionmentioning
confidence: 66%
“…Rey et al reported that RvE1 decreased LPSinduced gene expression of proin ammatory cytokines (TNF-α and IL-6), suggesting that they exerted proresolutive activity in microglia [29]. Wang et al reported that RvE1 treatment improved allogeneic corneal graft survival by signi cantly reducing the mRNA expression of proin ammatory cytokines, including TNF-α, IL-6 and IFN-γ, in corneal grafts, as well as the protein level of the proin ammatory cytokines TNF-α, IL-6 and IFN-γ [30]. However no similar ndings have been reported in the inner ear.…”
Section: Discussionmentioning
confidence: 99%